The “novel” of Artigas in the Manual de la Historia Argentina, by Vicente Fidel López (Quinto Sol, 2013)
The purpose of this work  is to analyse the way in which Vicente Fidel López, frames what we call “the novel of Artigas” in his Manual de la Historia Argentina, dedicado a los profesores y maestros que la enseñan (Textbook of Argentine History, devoted to professors and teachers who teach it), whose first edition was published in 1896. López's historiographic work is a development from his   literary activity, since -in his opinion- apart from being a scientific process, history implies an ability for evocation and dramatic re-creation that only an artist's sensitivity can put across. In the Manual, read and transmitted by several  generations of argentine normalistas, we are especially interested in examining the manner in which López rhetorically constructs Artigas' character as the paradigm of the caudillo (leader) in which all barbarie (barbarity) vices are incarnated; and also, the way in which this portrait is extrapolated at the momento of the enunciation-writing of the text, to warn young generations of criollos against the new enemies of the Nation that, by the late 19th century, were not the caudillos but socialists and anarchists who had arrived at the country with the migratory flow.
Keywords: Historiography; caudillos; Vicente Fidel Lopez; narrative